Synthesis of eco-friendly lipid-magnetite nanocomposite encapsulated Poinciana extract as promising insecticide against Culex pipiens - Ibrahim Taha Radwan; Noha Bagato; Manal S. Ebaid; Maysa M. Hegazy; Mohamed A. Farghali; Abdelfattah Selim; Hattan S. Gattan; Mohammed H. Alruhaili; Mohamed M. Baz; Abeer Mousa Alkhaibari (Scientific Reports)
Abstract Mosquito-borne diseases represent a growing health challenge over time. Nanostructured lipid carriers (NLCs) are the second generation of solid lipid nanoparticles (SLNs), and they continue to attract significant interest as potential diagnostic and therapeutic tools in disease inhibition and insect control. Activated ingredients presented in the Poinciana leaves were extracted and GC–MS data indicated an increased abundance of terpenes, flavonoids, and phenolic substances. Poinciana extract was encapsulated to the vicinity of nanostructure lipid carrier, Po-NLC, and surface modified with magnetic nanoparticles, Po-NLC-MNPs. The synthesized nanoparticles depicted average particle size of 73.2 and 75.55 nm while zeta potential of (− 29.4) and (‒ 4.44 mV) for Po-NLC and Po-NLC-MNPs, respectively. Transmission electron microscope and morphology determination showed regular, irregular spherical and oval shapes with diverse single particle size. X-rays diffraction pattern of the freely synthesized MNPs was compared to the decorated NLC and the results manifested that the NLC was successfully decorated with MNPs. The larvicidal activity of plant extract, Poinciana extract (Po), and their nanoparticle conjugates against 3rd instar larvae of Culex pipiens was evaluated at 50, 100, 200, 500, 1000, and 1500 ppm concentrations. Both high and low concentrations of Po-NLC-MNPs, indicated potential larval mortality than plant extracts (Po extract) itself. The mortality rate reached 100% for 3rd instar larvae. Based on their relative toxicity, (Po-NLC-MNPs) was the best at killing larvae, followed by Po-NLC. The synthesized nps were checked for their cytotoxic effect against wi38 cell line. The in-vitro cytotoxicity results indicated that there was no significant cytotoxicity and the nanocomposite barely caused weak changes in the tested cells. The synthesized nanoparticles have potential to create a new generation of eco-friendly, effective alternatives for controlling mosquito-borne diseases.